Scientific Production of occupational therapy in the school inclusion: interface with the Special Education and contributions to the field - Aline Cirelli Coppede; Alyne Kalyane Câmara de Oliveira; Fernanda Duarte Rosa; Maria Cristina Piumbato Innocentini Hayashi (Universidade Federal de Santa Maria (UFSM), 2014)
A strategy, which has been proved productive to inclusive education, was put into practice, in an effective way, by the education and health professionals partnership. The occupational therapist (OT) presents, in its formation, characteristics which enable them to frame as important elements in the process of improvement in the school inclusion. It aims to characterize the national scientific production about occupational therapy contributions for school inclusion process, through an exploratory and descriptive search, with a bibliometric approach. The search was performed in the databases BVS, Scielo, Redalyc and periodics Cadernos de Terapia Ocupacional da UFSCar, Revista de Terapia Ocupacional da USP, Revista Brasileira de Educação Especial e Revista Educação Especial da UFSM, using the search expressions "occupational therapy", "school inclusion", "especial education", "inclusive education" "school context", "assistive technology" and "school". With the aid of software VantagePoint®, the analysis produced indicators: year of publication, major journals when these papers were published, authors who participated in more publications, main topics discuted. Results pointed some characteristics of the literature of the field, highlighting the growing number of publishing in the last two years; publication predominance in occupational therapy journals; small group of authors responsible for the majority of publications, most studies are original, review, exploratory and descriptive, being the most common theme regarding questions about the role of OT in school inclusion processes, these data that characterize the scientific and reveal important contributions of occupational therapy in the context of inclusive education.